The impact of land use and land cover change on hydrological processes in Brantas watershed, East Java, Indonesia - Mohamad Wawan Sujarwo; Indarto Indarto; Marga Mandala (Kuwait Journal of Science)
Assessing the impact of land use and land cover (LULC) change on hydrology is essential for water resource management. The Brantas watershed contributes about 30% of the water supply in the East Java region. The rise and rapid change of land occupation for agriculture and settlements are supposed to alter the hydrological processes. This study aims to simulate the LULC change and its impact on the hydrological process on the watershed.  The long-period of LULC change impact is evaluated using the Soil & Water Assessment Tool (SWAT). The model is calibrated using monthly data series from 1996 to 2005 and then validated using series data from 2006 to 2015. Two editions of maps ( 2001 and 2015) are used to calculate the LULC changes.  The results show the increase of all hydrological components in the watershed.  The variability of rainfall patterns from 2001 to 2015 strongly affect the hydrological processes. The impact of LULC change on hydrological processes at the sub-basin level are also evaluated and compared.